A Comparative Study of Redox Mediators for Improved Performance of Li–Oxygen Batteries. Issue 27 (5th June 2020) - Zhang, Chengji; Dandu, Naveen; Rastegar, Sina; Misal, Saurabh N.; Hemmat, Zahra; Ngo, Anh T.; Curtiss, Larry A.; Salehi‐Khojin, Amin
Abstract: Redox meditators (RMs) are soluble catalysts located in an electrolyte that can improve the energy efficiency (reduced overpotential) and cyclability of Li–oxygen (Li–O2 ) batteries. In this work, 20 RMs within a Li–O2 system with dimethyl sulfoxide and tetraethylene glycol dimethyl ether electrolytes are studied and their electrochemical features such as redox potential, the separation of cathodic and anodic peaks, and their current intensities are measured using cyclic voltammetry (CV) experiments. Six RMs are selected as "primary" choices based on their electrochemical performance, and stability tests are then performed to examine their electrochemical responses after consecutive cycles. Moreover, galvanostatic cycling tests are performed within a Li–O2 battery system assembled with selected six RMs for real case consistency investigations. It is found that results from CV to galvanostatic cycling tests are consistent for halides and organometallic RMs, where the former exhibit much higher stability. However, the organic RMs show high reversibility in CV but low in battery cycling results. Density functional theory calculations are carried out to gain more understanding of the stability and redox potentials of the RMs. This study provides comparative information to select the most reliable RMs for Li–O2 batteries along with new fundamental understanding of their electrochemical activity and stability. Abstract : Various redox mediators, which can act as effective catalysts in Li–O2 batteries during charge, are examined under identical conditions for their electrochemical characteristics such as redox potential and stability. Further investigations including performance in batteries and density functional calculations provide fundamental understanding of the use of each redox mediator in Li–O2 batteries.